The Art of Lecturing A Practical Guide to Successful University Lectures and Business Presentations - Aarabi, Parham (Cambridge University Press, 2013)
This book and the contents therein have been made possible by the direct and indirect advice and help of numerous individuals, including Professors Jonathan Rose, Amir Keyvan Khandani, Ladan Tahvildari, Tarek Abdelrahman, Paul Chow, Sergei Dmitrevsky, Brendan Frey, Zvonko Vranesic, Lambertus Hesselink, Bernard Widrow, and Safwat Zaky. Without their contributions and help, I would still be a struggling lecturer back at Stanford University. Finally, the thousands of students whom I have had the pleasure of instructing in classes are the cornerstone of the ideas in this book. Their advice, feedback, comments, questions, and complaints were like navigation beacons that have to this day guided me through the murky waters of lecturing dos and don’ts.